منهج القرآن في إدارة الأزمة السياسة -سليمان عليه السلام مع ملكة مملكة سبأ-نموذجاً - Reem Ahmed Abdel Majeed Al-Maghribi; Kauthar Abd Kadir; Ahmad Kamel Mohamad (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies